Green Finance: An Emerging Prospective towards Sustainable Development in India - Sandeep Kumar Rawat, Dr. Anu (International Journal of Advanced Science and Technology, 2020)
Environmental sustainability means prevention of waste full use of the natural resources and protecting these resources for the future   generation. Environmental sustainability has become one of the biggest challenges for the every country in the world; none of the country remains untouched with the problem of natural resource degradation. Every country in world trying to solve this problem through many ways green finance is one the powerful weapon to achieve the goal of sustainable development among them. Green finance refers to those processes which amalgamate the finance and its instruments with environmental sustainability and social profitability. It uses the financial instruments which has the quality of profitability with sustainability.  This study describes the phenomena of green finance, its relevance and its adoption in Indian context. This study also elucidates the status of green finance in India.